(untitled) (Junior Management Science, 2017)
This study focuses on the widely spread concept of User-Centered Design (UCD) and tries to answer the question why it is so popular. On the one hand, it is of interest to reveal the nature of UCD, especially in terms of the methods used, the types of users involved and the stages the involvement takes place. On the other hand, this paper aims to find out about the success of UCD projects as well as the organizational context that is beneficial for UCD. To do so, several streams of scientific literature in the field of UCD as well as organization theory are reviewed and the results of an empirical study conducted among UCD experts in Germany are analyzed. The theoretically derived characteristics could mainly be confirmed by the insights of the study. Moreover, several hypotheses concerning the influence of the organizational context using established constructs (IT competence, UCD competence, customer orientation, innovativeness, exploration and exploitation as well as the top management team) towards the project success in an UCD setup are proposed and tested by the means of a multiple factor analysis. By analyzing open comments concerning the facilitators and obstacles of UCD activities deeper insight into the daily business of UCD experts can be gained. A comparison between two subsamples split according to their project success score yield interesting results concerning different motives, types of integrated users and the locus of the user integration. This study has been created in collaboration with the user research and user experience (UX) consulting agency ‘Facit Digital’ who are based in Munich, Germany.Keywords: User-Centered Design, User Integration, Exploration, Exploitation, Empirical Investigation